Assessment of muscle oxygenation following eccentric exercise-induced muscle damage using near-infrared spectroscopy - Chris McManus; Kelly Murray; Elizabeth Welbourn; Julie Double; Henry Chung; Sally Waterworth; Ben Jones; Chris Cooper (PLoS ONE, 2026)
Exercise-induced muscle damage (EIMD) disrupts muscle structure and function, impairing recovery and performance. Near-infrared spectroscopy (NIRS) offers a non-invasive method to assess muscle oxygenation, yet its sensitivity to EIMD-related changes under practical conditions remains unclear. This study examined whether resting tissue saturation index (TSI) and sprint-phase oxygenation kinetics are altered following EIMD. Seventeen recreationally active males were assigned to a control (n = 5) or experimental group (n = 12). The experimental group performed 10 × 10 eccentric squats at 80% 1RM. Resting TSI, sprint-phase desaturation/resaturation, countermovement jump (CMJ), wellness, and creatine kinase (CK) were measured at baseline and 1, 24, 48, 72, and 96 hours post-exercise. Control data provided typical error and smallest worthwhile change thresholds for reliability and interpretation. No statistically significant differences were found over time or between groups for CK, performance, or NIRS variables ( P > 0.05). However, effect size-based inferences revealed small to extremely large effect sizes in CMJ, wellness, CK, and key NIRS metrics. Notably, desaturation amplitude and rate during Sprint 1 showed large effects at 1 h post-EIMD, while resting TSI demonstrated a small increase at 24 h. These observations indicate that resting TSI and selected sprint-phase NIRS indices exhibit small but systematic changes in temporal association with an eccentric squat protocol that induces EIMD, and suggest that NIRS may have the potential to contribute to non-invasive characterisation of muscle status in this context.